ANALISIS STRUKTUR PENDAPATAN, POLA KONSUMSI DAN KESEJAHTERAAN RUMAHTANGGA PETANI SAYURAN DI KABUPATEN SIAK - Vera Gustika Salni; Djaimi Bakce; Ermy Tety (Indonesian Journal of Agricultural Economics, 2019)
The purpose of this study is to know how the structure of income, consumption patterns and welfare and know the dominant factors that affect the pattern of household consumption of vegetable farmers in Siak District. The purpose of this study will be answered by analyzing the income structure, logistic regression method and poverty line approach. Based on the results of the analysis obtained the largest source of income comes from work income is vegetable farming. For the consumption of household expenditures, the largest expenditure made for non-food needs is greater than food expenditure. This indicates that households of vegetable farmer in Siak Regency are classified as prosperous. The dominant factors affecting the consumption pattern of household food of vegetable farmers are income, the number of family members and health investment. Thus, to improve the prosperity of households of vegetable farmers, it is necessary to increase household income by improving cultivation techniques and increasing farmers' selling price and knowledge. Besides that, there should be extension about the importance of education and counseling about family planning program to minimize household food expenditure of vegetable farmers.